Regional State vs. Federal State for Colombia - Sanabria Buitrago, Pedro Alonso (Universidad Pedagógica y Tecnológica de Colombia, 2003)
Since the beginning of the Republic, in Colombia there has been a strong confrontation on the form of State to adopt, following the French and North American models; confrontation that regains validity in our times when the 1991 Constitution establishes the possibility of constituting regions in the country as territorial entities, which found a new model of State: the Regional. Undoubtedly, the Italian and French experiences on the subject have influenced our environment, where the clamor of the territorial entities that demand greater powers and a broader and more effective autonomy joins the debate on the convenience of adopting a form of State Federal, for some, or a Regional State, for others.